New results on helix surfaces in the Minkowski 3-space - Kelleci, Alev; Turgay, Nurettin Cenk; Ergut, Mahmut (Int Electronic Journal Geometry, 2019)
In this paper, we characterize and classify helix surfaces with principal direction relatived to a space-like and light-like, constant direction in the Minkowski 3-space.
Keywords: Minkowski space; Space-like surfaces; constant angle surfaces